Screening Ethanol-Producing Yeast Origin from Pineapple Honey Ananas comosus (L.) Merr var Quenn - Sutoyo, Sutoyo; Siswanto, Siswanto (Department of Biology, Faculty Mahematics and Natural Sciences, University of Jember, 2023)
The availability of fossil-based fuels will gradually decrease while the amount required increases. This has prompted research to find alternative energy sources, including bioethanol. Bioethanol, as an alternative energy source, can be used as a transportation fuel better than fossil-based fuels because ethanol has a high octane number, laminar velocity and heat of vaporisation. Meanwhile, the level of carbon and hydrocarbon emissions is low so it can increase combustion efficiency in vehicles. In addition, the use of bioethanol as fuel is environmentally friendly and renewable. Ethanol can be produced through a fermentation process using ethanol-producing yeast. Pineapple honey is known for its high sugar and other nutrient content, so it is supposed that many types of yeast can grow well in it. This study aims to isolation and screening of bioethanol-producing yeast from Pineapple Honey. This study was carried out by yeast isolation method, primary yeast screening, secondary yeast screening, and characterisation of selected yeast isolates. Data on ethanol production by yeast isolates were analysed by ANOVA with Î±=0.05 using the R studio program. This primary isolation and screening phase found eight yeast isolates capable of fermenting glucose and producing acid and gas in the test medium. Test ethanol production in DPE medium with 18% glucose content on all isolates showed that all isolates could produce ethanol with a range of 4.20-10.35%. Isolates of IK4 showed the highest ethanol production ability (10.35%) (p<0.5%) in significant contrast to the other seven isolates. Based on macroscopic and microscopic morphological characterisations, IKM 4 isolates show similarities to the genus Saccharomyces Keywords: ethanol, pineapple, yeasts